2015
DOI: 10.3923/tasr.2015.166.174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Cognitive Performance in Egyptian School-Age Children

Abstract: Childhood obesity is considered to be major concern that puts children at increased risk of poor cognitive functions, physical health and later in life they may develop many chronic diseases. The purpose of the study is to investigate the effect of obesity on children's developmental trajectories of cognitive functions (sustained attention, memory, logical thinking and executive functions) of the obese and normal Egyptian school-age children and to investigate if the BMI can be used as a predictor of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although some studies found that obesity affects cognitive function, other studies suggested that cognitive function in healthy children and adolescents is not associated with high BMI [21-24]. However, in other previous studies, the obese group, relative to the non-obese group, showed a weaker inhibitory control of attention in the visuospatial attention task.…”
Section: Discussionmentioning
confidence: 75%
“…Although some studies found that obesity affects cognitive function, other studies suggested that cognitive function in healthy children and adolescents is not associated with high BMI [21-24]. However, in other previous studies, the obese group, relative to the non-obese group, showed a weaker inhibitory control of attention in the visuospatial attention task.…”
Section: Discussionmentioning
confidence: 75%
“…In Egypt, the prevalence of overweight and obesity among school age children in 2013 was 17.7 and 13.5%, respectively. (EL-Gilany, 2011 andAmeen andAbdelazeim, 2015) stated that obesity is a public health priority because it is associated with a diverse range of morbidities and it may interfere with normal psychosocial, emotional, and physical development.…”
Section: Significance Of the Studymentioning
confidence: 99%